A lithium ion battery composite negative electrode and preparation method thereof

By adopting the synergistic effects of negative electrode prelithiation and electrolyte in situ polymerization in lithium-ion batteries, and using high melting point polymer surface coating technology, the problem of synergistic preparation of prelithiation and in situ polymerization in the prior art is solved, and the energy density and safety of the battery are improved.

CN119764354APending Publication Date: 2025-04-04CHINA POWER TECH INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411888555.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art cannot achieve the coordinated preparation of prelithiation of lithium-ion batteries and in-situ polymerization, and cannot further improve the safety performance by improving the insulation characteristics of the positive and negative electrodes.

Method used

The synergistic effect of the negative electrode prelithiation and electrolyte in-situ polymerization reaction is adopted, and the prelithiation of the negative electrode of lithium-ion battery and the in-situ preparation of the negative electrode protective layer of the negative electrode are achieved through high melting point polymer surface coating technology.

Benefits of technology

The first efficiency, energy density and intrinsic safety of lithium-ion batteries have been improved, and the reaction is uniform and controllable, making it easy to achieve industrial preparation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a composite negative electrode for lithium ion batteries and a preparation method thereof, comprising mixing and homogenizing the negative electrode material with a binder, a conductive agent and a solvent respectively, coating, drying and shearing to prepare the negative electrode sheet of the lithium ion battery; dispersing lithium powder in toluene or xylene to prepare a pre-lithiation slurry; dissolving a certain amount of polymer monomer 2-cyano-ethyl acrylate and a high melting point polymer in a volatile small molecule solvent, fully dissolving and preparing a polymer monomer and a high melting point polymer mixed solution; coating the pre-lithiation slurry on the negative electrode sheet, drying to obtain a pre-lithiation negative electrode sheet; coating the polymer monomer and the high melting point polymer mixed solution on the pre-lithiation negative electrode sheet, drying to obtain a composite negative electrode sheet for lithium ion batteries. The synergistic effect of negative electrode pre-lithiation and electrolyte in-situ polymerization reaction is utilized, and at the same time, the high melting point polymer surface coating technology is adopted to realize the pre-lithiation of the negative electrode of the lithium ion battery and the in-situ preparation of the negative electrode protective layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery composite negative electrode and a preparation method thereof. Background Art

[0002] As the energy density and safety performance of lithium-ion batteries face increasing challenges, the safety performance of high-energy-density lithium-ion batteries has attracted much attention.

[0003] Silicon-based materials with high theoretical gram capacity are an important solution to improve the energy density of lithium-ion batteries. Silicon oxide materials are widely used due to their good comprehensive performance. Their theoretical gram capacity is 1964mAh / g, but their initial efficiency (65%-85%) is low. In addition, whether it is a graphite negative electrode or a silicon negative electrode material, the formation of the SEI film requires the consumption of a portion of the lithium ions from the positive electrode, which affects the capacity of the positive electrode material. Lithium metal has a natural advantage as the negative electrode of lithium-ion batteries. The theoretical specific capacity of metallic lithium is 3860mAh / g, which can compensate for the irreversible lithium loss caused by the battery charging and discharging process by pre-lithiation of the negative electrode. In addition, lithium metal can also catalyze the polymerization reaction of some polymer monomers and play an important role in polymer preparation.

[0004] CN107658500A invented a method and application of in-situ preparation of flexible lithium-ion battery polymer electrolyte. Secondary lithium-ion batteries with gel-type polymer as electrolyte have good chemical and electrochemical stability. However, gel electrolyte does not have a mutual promotion effect with the functional substances in the conductive agent, and cannot achieve more effective structural and performance improvements.

[0005] CN115621528B provides a method for pre-lithiation of a negative electrode of a battery, comprising: adding metallic lithium to an organic solution of an aromatic hydrocarbon substance under an inert atmosphere to react and obtain an aryl lithiation reagent; immersing the negative electrode sheet in the aryl lithiation reagent to perform a pre-lithiation reaction, then taking out the negative electrode sheet after the reaction, washing and drying, and obtaining a pre-lithiation negative electrode sheet. This invention does not utilize the synergistic effect of in-situ preparation of lithium metal and polymer.

[0006] CN118738296A achieves pre-lithiation of silicon negative electrode sheets by allowing metal lithium sheets to directly contact with silicon negative electrode sheets under the infiltration of electrolyte, and controls the degree of pre-lithiation by controlling the contact time. This application can achieve simple and convenient pre-lithiation of silicon negative electrode sheets without introducing impurities, preserving the original morphology of silicon negative electrode active particles, and reducing the internal resistance of the battery, significantly improving the first coulomb efficiency, and at the same time, the silicon negative electrode after pre-lithiation has better rate performance and cycle performance due to the relief of volume expansion during the cycle process. This invention does not utilize the synergistic effect of in-situ preparation of lithium metal and polymer.

[0007] The above technology cannot achieve the coordinated preparation of lithium-ion battery pre-lithiation and in-situ polymerization, and cannot further improve the safety performance by improving the insulation properties of the positive and negative electrodes. There are obvious shortcomings. Summary of the invention

[0008] In view of the problems existing in the prior art, the present invention provides a lithium-ion battery composite negative electrode and a preparation method thereof, which utilizes the synergistic effect of negative electrode pre-lithiation and electrolyte in-situ polymerization reaction. At the same time, a high melting point polymer surface coating technology is adopted to achieve the pre-lithiation of the lithium-ion battery negative electrode and the in-situ preparation of the negative electrode protective layer.

[0009] The present invention is achieved by a method for preparing a composite negative electrode for a lithium ion battery, comprising the following steps:

[0010] The first step is to prepare the negative electrode sheet of the lithium-ion battery: the negative electrode material is mixed with the binder, the conductive agent and the solvent respectively and homogenized, and then coated, dried and sheared to prepare the negative electrode sheet of the lithium-ion battery;

[0011] The second step is to prepare a pre-lithiation slurry: disperse lithium powder in toluene or xylene to prepare a pre-lithiation slurry;

[0012] The third step is to prepare a mixed solution of polymer monomer and high melting point polymer: a certain amount of polymer monomer 2-cyano-ethyl acrylate and high melting point polymer are dissolved in a volatile small molecule solvent, and fully dissolved to prepare a mixed solution of polymer monomer and high melting point polymer;

[0013] The fourth step is to apply the pre-lithiation slurry on the negative electrode sheet and dry it to obtain the pre-lithiation negative electrode sheet;

[0014] The fifth step is to apply the mixed solution of the polymer monomer and the high melting point polymer on the pre-lithiated negative electrode sheet and dry it to obtain a composite negative electrode sheet for a lithium-ion battery.

[0015] In the first step, the negative electrode material of the lithium-ion battery includes graphite, soft carbon, hard carbon, SiO x, Si / C traditional lithium-ion battery negative electrode materials; the binder includes at least one of polyimide PI, PVDF, SBR, CMC, PPC, and PEO.

[0016] In the second step, in the pre-lithiation slurry, the mass of lithium powder accounts for 1%-5% of the mass of the slurry.

[0017] In the third step, the mass content of the polymer monomer 2-cyano-ethyl acrylate is 1%-20%, the mass content of the high melting point polymer is 1-20%, and the mass content of the small molecule solvent is 60-98%.

[0018] In the third step, the high melting point polymer is PI or PET.

[0019] The small molecule solvent is at least one of dimethyl carbonate DMC, nitrogen methyl pyrrolidone NMP, acetonitrile, tetrahydrofuran, toluene or xylene.

[0020] In the third step and the fourth step, during pre-lithiation, the lithium mass per unit area is 0.05-0.3 mg / cm 2 , the drying temperature is 60-90℃.

[0021] The lithium ion battery composite negative electrode prepared by the above preparation method.

[0022] The advantages and technical effects of the present invention are as follows: The present invention utilizes the synergistic effect of negative electrode pre-lithiation and electrolyte in-situ polymerization reaction, and at the same time, adopts high melting point polymer surface coating technology to achieve the pre-lithiation of the negative electrode of the lithium-ion battery and the in-situ preparation of the negative electrode protective layer. Pre-lithiation and surface functionalization can be efficiently achieved to improve the initial efficiency, energy density and intrinsic safety of lithium-ion batteries. The method has uniform and controllable reaction and is easy to achieve industrial preparation. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] The method for preparing the composite negative electrode of a lithium ion battery of the present invention comprises the following steps:

[0025] The first step is to prepare the negative electrode sheet of the lithium-ion battery: the negative electrode material is mixed with the binder, the conductive agent and the solvent respectively and homogenized, and then coated, dried and sheared to prepare the negative electrode sheet of the lithium-ion battery;

[0026] The second step is to prepare a pre-lithiation slurry: disperse lithium powder in toluene or xylene to prepare a pre-lithiation slurry;

[0027] The third step is to prepare a mixed solution of polymer monomer and high melting point polymer: a certain amount of polymer monomer 2-cyano-ethyl acrylate and high melting point polymer are dissolved in a volatile small molecule solvent, and fully dissolved to prepare a mixed solution of polymer monomer and high melting point polymer;

[0028] The fourth step is to apply the pre-lithiation slurry on the negative electrode sheet and dry it to obtain the pre-lithiation negative electrode sheet;

[0029] The fifth step is to apply the mixed solution of the polymer monomer and the high melting point polymer on the pre-lithiated negative electrode sheet and dry it to obtain a composite negative electrode sheet for a lithium-ion battery.

[0030] In the first step, the negative electrode material of the lithium-ion battery includes graphite, soft carbon, hard carbon, SiO x , Si / C traditional lithium-ion battery negative electrode materials; the binder includes at least one of polyimide PI, PVDF, SBR, CMC, PPC, and PEO.

[0031] In the second step, in the pre-lithiation slurry, the mass of lithium powder accounts for 1%-5% of the mass of the slurry.

[0032] In the third step, the mass content of the polymer monomer 2-cyano-ethyl acrylate is 1%-20%, the mass content of the high melting point polymer is 1-20%, and the mass content of the small molecule solvent is 60-98%.

[0033] In the third step, the high melting point polymer is PI or PET.

[0034] The small molecule solvent is at least one of dimethyl carbonate DMC, nitrogen methyl pyrrolidone NMP, acetonitrile, tetrahydrofuran, toluene or xylene.

[0035] In the third step and the fourth step, during pre-lithiation, the lithium mass per unit area is 0.05-0.3 mg / cm 2 , the drying temperature is 60-90℃.

[0036] The lithium ion battery composite negative electrode prepared by the above preparation method.

[0037] The present invention utilizes the synergistic effect of negative electrode pre-lithiation and electrolyte in-situ polymerization reaction, and at the same time, adopts high melting point polymer surface coating technology to achieve the pre-lithiation of the negative electrode of the lithium ion battery and the in-situ preparation of the negative electrode protective layer. The pre-lithiation is an in-situ solid phase reaction between the negative electrode of the lithium ion battery and metallic lithium. The electrolyte in-situ polymerization reaction is an in-situ polymerization reaction of 2-cyano-ethyl acrylate under the catalysis of lithium metal. The two in-situ reactions have a synergistic effect. The pre-lithiation reaction of the negative electrode of the lithium ion battery reduces the irreversible capacity of the negative electrode. At the same time, the fresh lithium and reaction heat generated at the reaction interface make it have higher catalytic activity. 2-cyano-ethyl acrylate undergoes in-situ polymerization reaction under the catalysis of lithium metal to generate a polymer protective film. The high melting point polymer is a high molecular polymer such as PI, PET, etc. Such polymers have a higher melting point than traditional diaphragms. The polymer coating layer and the in-situ polymerized electrolyte are mutually entangled and combined through intermolecular forces such as hydrogen bonds, which greatly improves the positive and negative electrode contact resistance during battery thermal runaway and reduces the risk of internal short circuits in the battery. The pre-lithiated lithium-ion battery negative electrode sheet achieves efficient pre-lithiation and surface functionalization treatment, thereby improving the initial efficiency, energy density and intrinsic safety of the lithium-ion battery. The method has uniform and controllable reaction and is easy to realize industrial preparation.

[0038] Example 1

[0039] A method for preparing a composite negative electrode sheet for a lithium-ion battery, the steps of the embodiment are as follows:

[0040] In the first step, according to the traditional lithium-ion battery manufacturing process, the negative electrode material is first mixed and homogenized with a binder, a conductive agent, a solvent (H2O), etc., coated on a 310mm wide * 4μm thick copper foil and dried to obtain the negative electrode sheet of the lithium-ion battery. The formula of the negative electrode sheet powder is: graphite, SiOx, PAA and CNT, with mass contents of 78%, 18%, 2.5% and 1.5% respectively.

[0041] In the second step, lithium powder is dispersed in toluene to prepare a 5% pre-lithiation lithium metal slurry.

[0042] The third step is to prepare a mixed solution of polymer monomer and high melting point polymer: 1% of polymer monomer 2-cyano-ethyl acrylate and 2% of PI are dissolved in acetonitrile and fully dissolved to prepare a mixed solution of 2-cyano-ethyl acrylate and PI.

[0043] Step 4: In an inert gas atmosphere glove box, the pre-lithiation slurry was coated on the negative electrode sheet and fully dried at 60°C to obtain 0.1 mg / cm 2 Pre-lithiation negative electrode sheet.

[0044] Step 5: In an inert gas atmosphere glove box, apply the polymer monomer and high melting point polymer mixed solution on the pre-lithiated negative electrode sheet and dry at 80°C. The polymer coating amount is controlled to be 0.1 mg / cm 2 , and obtain a composite negative electrode sheet for a lithium-ion battery.

[0045] Example 2

[0046] A method for preparing a composite negative electrode sheet for a lithium-ion battery, the steps of the embodiment are as follows:

[0047] In the first step, according to the traditional lithium-ion battery manufacturing process, the negative electrode material is first mixed and homogenized with a binder, a conductive agent, a solvent (H2O), etc., coated on a 310mm wide * 4μm thick copper foil and dried to obtain the negative electrode sheet of the lithium-ion battery. The formula of the negative electrode sheet powder is: graphite, SiOx, SiC, PAA, SBR, CMC and CNT, with mass contents of 78%, 10%, 8%, 2.0%, 0.3%, 0.2% and 1.5% respectively.

[0048] In the second step, lithium powder is dispersed in toluene to prepare a 3% pre-lithiation lithium metal slurry.

[0049] The third step is to prepare a mixed solution of polymer monomer and high melting point polymer: 1% of polymer monomer 2-cyano-ethyl acrylate and 2% of PET are dissolved in acetonitrile, and fully dissolved to prepare a mixed solution of 2-cyano-ethyl acrylate and PI.

[0050] In the fourth step, in an inert gas atmosphere glove box, the pre-lithiation slurry was coated on the negative electrode sheet and fully dried at 80°C to obtain 0.06 mg / cm 2 Pre-lithiation negative electrode sheet.

[0051] Step 5: In an inert gas atmosphere glove box, apply the polymer monomer and high melting point polymer mixed solution on the pre-lithiated negative electrode sheet and dry at 80°C. The polymer coating amount is controlled to be 0.1 mg / cm 2 , and obtain a composite negative electrode sheet for a lithium-ion battery.

[0052] Test Results

[0053] Example 1 Negative electrode sheet testing method:

[0054] According to the general preparation method of lithium-ion batteries, the negative electrode sheet of Example 1 and the comparative negative electrode sheet (the non-pre-lithiation electrode sheet prepared in the first step of Example 1) were assembled into a lithium-ion battery, and a lithium cobalt oxide positive electrode system (LCO: binder: conductive agent = 97.8%: 1.2%: 1%), conventional lithium-ion battery electrolyte, separator, etc. were used to assemble a 4160143 (4.1mm*60mm*143mm) type lithium-ion soft pack battery. The test was carried out using conventional lithium-ion battery testing equipment (Arbin).

[0055] Example 1 Negative electrode sheet test results

[0056] Discharge capacity First efficiency Energy density Cycle retention rate Compare Batteries 4.83Ah 89.6% 296Wh / kg 96%@60 cycles Pre-lithiation battery 5.17Ah 80.9% 276Wh / kg 94%@60 cycles

[0057] Example 2 Negative electrode sheet testing method:

[0058] According to the general preparation method of lithium-ion batteries, the negative electrode sheet of Example 2 and the comparative negative electrode sheet (the non-pre-lithiation electrode sheet prepared in the first step of Example 2) were assembled into lithium-ion batteries, and NCM ternary positive electrode system (NCM811: binder: conductive agent = 97.8%: 1.2%: 1%), conventional lithium-ion battery electrolyte, separator, etc. were used to assemble 0960143 (9.0mm*60mm*143mm) type lithium-ion soft pack batteries. Conventional lithium-ion battery testing equipment (Arbin) was used for testing.

[0059] Example 2 Negative electrode sheet test results

[0060] Discharge capacity First efficiency Energy density Cycle retention rate Compare Batteries 10.9 86.% 300Wh / kg 92%@200 cycles Pre-lithiation battery 11.16 88.2% 308Wh / kg 95%@200 cycles

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite negative electrode for a lithium ion battery, characterized in that: The following steps are involved: The first step is to prepare the negative electrode sheet of the lithium-ion battery: the negative electrode material is mixed with the binder, the conductive agent and the solvent respectively and homogenized, and then coated, dried and sheared to prepare the negative electrode sheet of the lithium-ion battery; The second step is to prepare a pre-lithiation slurry: disperse lithium powder in toluene or xylene to prepare a pre-lithiation slurry; The third step is to prepare a mixed solution of polymer monomer and high melting point polymer: a certain amount of polymer monomer 2-cyano-ethyl acrylate and high melting point polymer are dissolved in a volatile small molecule solvent, and fully dissolved to prepare a mixed solution of polymer monomer and high melting point polymer; The fourth step is to apply the pre-lithiation slurry on the negative electrode sheet and dry it to obtain the pre-lithiation negative electrode sheet; The fifth step is to apply the mixed solution of the polymer monomer and the high melting point polymer on the pre-lithiated negative electrode sheet and dry it to obtain a composite negative electrode sheet for a lithium-ion battery.

2. The method for preparing a composite negative electrode for a lithium-ion battery according to claim 1, characterized in that: In the first step, the negative electrode material of the lithium-ion battery includes graphite, soft carbon, hard carbon, SiO x , Si / C traditional lithium-ion battery negative electrode materials; the binder includes at least one of polyimide PI, PVDF, SBR, CMC, PPC, and PEO.

3. The method for preparing a composite negative electrode for a lithium ion battery according to claim 1, characterized in that: In the second step, in the pre-lithiation slurry, the mass of lithium powder accounts for 1%-5% of the mass of the slurry.

4. The method for preparing a composite negative electrode for a lithium ion battery according to claim 1, characterized in that: In the third step, the mass content of the polymer monomer 2-cyano-ethyl acrylate is 1%-20%, the mass content of the high melting point polymer is 1-20%, and the mass content of the small molecule solvent is 60-98%.

5. The method for preparing a composite negative electrode for a lithium ion battery according to claim 1 or 4, characterized in that: In the third step, the high melting point polymer is PI or PET.

6. The method for preparing a composite negative electrode for a lithium ion battery according to claim 1 or 4, characterized in that: The small molecule solvent is at least one of dimethyl carbonate DMC, nitrogen methyl pyrrolidone NMP, acetonitrile, tetrahydrofuran, toluene or xylene.

7. The method for preparing a composite negative electrode for a lithium-ion battery according to claim 1, characterized in that: In the third step and the fourth step, during pre-lithiation, the lithium mass per unit area is 0.05-0.3 mg / cm 2 , the drying temperature is 60-90℃.

8. A lithium-ion battery composite negative electrode prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparing polymer electrolyte of flexible lithium-ion battery in situ and application

    CN107658500A